Helsinki framework: Co-design of principles for sustainability education - Vesterinen, Veli-Matti (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
In this paper I discuss the creation of the Helsinki Framework, which is one of the major outcomes of ActSHEN. It represents elements that project team members saw as central to working with sustainability education. The purpose of the framework is to provide ideas for embedding sustainability awareness and action in higher education. The creation of the framework was a messy affair, as such collaborative design processes tend to be. To make sense of this mess, I will present here a design narrative (see Bell, Hoadley & Linn, 2004), which describes what happened during the design process. It is written from my personal point of view.